Post-Conditioning and Reperfusion Injury in the Treatment of Stroke - Roger Simon (SAGE Publishing, 2014)
Endogenous mechanisms of protection against ischemia can be demonstrated in brain and other organs. The induction of such protection is via a response to sub lethal stress which induces "preconditioning". The preconditioned organ is then "tolerant" to injury from subsequent severe stress of the same or different etiology. Protection is substantial (70% reduction) but delayed in onset and is transient. Gene expression is unique between brains preconditioned, injured (stroke) or made tolerant. Thus, preconditioning reprograms the response to lethal ischemic stress (stroke), reprogrammed from an injury induction response to a neuroprotective processes. Postconditioning refers to attenuation of injurious processes occurring during reperfusion of ischemic brain. Transient mechanical interruption of reperfusion induces post-conditioning which can attenuate reperfusion injury. Post-conditioning protects ischemic brain by decreasing reperfusion induced oxygen free radical formation. The free radicals produce injury via mitochondrial damage which can be repaired experimentally. Post-conditioning produces neuroprotection as potent as experimental preconditioning. The recognition of broad based gene silencing (suppression of thousands of genes) as the phenotype of the preconditioned, ischemic tolerant brain, may explain failure of all single target drugs for stroke. As risks of reperfusion injury accompany treatment for acute stroke, endogenous neuroprotective and repair mechanisms offer translational stroke therapy.